(untitled) (CIPEEX, 2023)
Circus activities are physical practices that involve elements such as juggling, balance, acrobatics, clowning, and magic. The main objective of the study is to analyze the goals of Circus Activities in the educational and professional spheres. It is a review study of research with a qualitative approach, characterized, in terms of objectives, as a bibliographic research of the exploratory descriptive type. A total of 5,963 articles were located. After analyzing the titles and abstracts of the articles, 5,933 were excluded for not being related to the descriptors and for being outside the predetermined year range. However, 30 publications were selected, of which 10 articles were not related to the topic and 16 were duplicates. Thus, 04 articles were used for analysis. Through the studies found, the research problem was addressed, as observed in the studies used. the inclusion of circus activities in the school environment is still not routine, due to the fact that professionals do not have mastery of the content and are always in their comfort zone applying the more well-known sports.